Izikhothane: Masculinity and class in Katlehong, a South African township - Richards, James Grant (My University, 2016)
ABSTRACT The following thesis explored a specific subculture called skhothane, or izikhothane in the plural, which has taken root amongst the male youth in South African townships. Izikhothane are primarily concerned with music, fashion, dance and linguistic prowess in relation to their counterparts. They performed against their counterparts in order to gain status, prestige, fame and renown. These in turn were exchanged in some instances for other desired outcomes such as access to women. This study explored the intersecting factors that have caused the rise and transformation of this subculture. The contextual factors can be understood as historical, economic, and social. Other factors such as masculinity, gender, race, ethnicity and class seem to be playing a role in the meanings that izikhothane make and the lenses through which the view themselves and their urban spaces. In addition to the above the izikhothane were looked at in relation to subcultures that were formed during apartheid, such as comrades, tsotsis, comtsotsis and pantsulas, for example. This has given an idea of the continuity associated with subcultures and the generational factors that lead to their formation. The frame work that was used, for the most part, to critically understand this practice was primarily taken from Foucault’s conception of space, Winnicott’s formulation of transitional spaces, Bourdieu’s ideas of capital, and Erikson’s work on youth identity.
Keywords: Skhothane; Identity; Masculinity; Fashion; South African townships; South African music